1991
DOI: 10.1016/s0022-5347(17)38476-8
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Human Papillomavirus in Prostate Tissues

Abstract: Specific human papillomavirus (HPV) types are associated with benign and malignant lesions of the anogenital region including the prostate gland. Using polymerase chain reaction (PCR) amplification of type-specific HPV sequences, we have assessed the prevalence of HPV DNA in prostate tissue from 88 individuals. Amplified sequences specific for HPV 16 were found in 34 of 56 benign prostatic hyperplasias and in 14 of 27 prostatic carcinomas. In contrast, HPV 18 was identified in only three benign hyperplasias an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 20 publications
1
42
0
1
Order By: Relevance
“…An association of prostate cancer with sexual history, particularly sexual transmitted diseases like HPV infection, has been reported in several studies (Adami et al, 2003;Korodi et al, 2005;Martinez-Fierro et al, 2010;Chen et al, 2011). Most investigations reported a high frequency of HPV infection in BPH and PCa samples (McNicol and Dodd, 1991;Silvestre et al, 2009;Aghakhani et al, 2011), other investigations found a possible association between HPV and prostate carcinogenesis (Silvestre et al, 2009). On the other hand, wide ranges of studies are not clearly understood any association between HPV infection and prostate carcinogenesis and refuse the causal role of HPV infection in progression of BPH (Dodd et al, 1993;Noda et al, 1998;Leiros et al, 2005;Gazzaz and Mosli, 2009;Aghakhani et al, 2011;Chen et al, 2011;Smelov et al, 2011).…”
Section: Discussionmentioning
confidence: 90%
“…An association of prostate cancer with sexual history, particularly sexual transmitted diseases like HPV infection, has been reported in several studies (Adami et al, 2003;Korodi et al, 2005;Martinez-Fierro et al, 2010;Chen et al, 2011). Most investigations reported a high frequency of HPV infection in BPH and PCa samples (McNicol and Dodd, 1991;Silvestre et al, 2009;Aghakhani et al, 2011), other investigations found a possible association between HPV and prostate carcinogenesis (Silvestre et al, 2009). On the other hand, wide ranges of studies are not clearly understood any association between HPV infection and prostate carcinogenesis and refuse the causal role of HPV infection in progression of BPH (Dodd et al, 1993;Noda et al, 1998;Leiros et al, 2005;Gazzaz and Mosli, 2009;Aghakhani et al, 2011;Chen et al, 2011;Smelov et al, 2011).…”
Section: Discussionmentioning
confidence: 90%
“…Following the removal of the duplicates (n=63), 238 studies were excluded based on titles and abstracts review, mainly as they were not relevant to the present analysis. From a full-text review of potentially relevant papers (n=47), 23 studies were excluded based on the following reasons: A total of 4 studies (10,(12)(13)(14) included the same data as previous articles (22,23), 7 studies lacked a control group (24)(25)(26)(27)(28)(29)(30) and 2 studies did not offer the pathological tissue information (31,32); others used bladder cancer cells (33), PCa cells (34) or expressed prostate secretion as the experiment material (35). The last 2 studies were unavailable for analysis (36,37).…”
Section: Resultsmentioning
confidence: 99%
“…The last 2 studies were unavailable for analysis (36,37). Finally, 24 papers (6,22,23, were included in the meta-analysis. The papers included were published between February, 1990 and January, 2015.…”
Section: Resultsmentioning
confidence: 99%
“…Before reviewing the various viruses detected in the prostate, we should bear in mind that there are two different clinical entities: benign prostate hyperplasia and carcinoma of the prostate. It is unknown whether benign prostate hyperplasia coexists with prostate cancer and has a common etiology or (211). However, no significant difference was observed between patients with benign disease and those with evidence of malignancy, with nearly half of the patients testing positive in each case.…”
Section: Human Prostatementioning
confidence: 99%